KINERJA GURU DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Niko Sudibjo; Edberg Warbung (Universitas La Tansa Mashiro, 2021)
Performance is an essential aspect of an organization. Therefore, organizations need to ensure that members provide positive performance for the achievement of organizational goals. One crucial aspect that influences performance is emotional intelligence. However, emotional intelligence alone is not enough, so it is also necessary to look at aspects of culture and leadership in organizations. This research studies the teachers' performance in Tunas Bangsa Greenville Middle and High School by looking at the influence exerted by the teacher's emotional intelligence, the principal's transformational leadership, and organizational culture. The data in the study were obtained by dividing the questionnaire, then analyzed quantitatively through the PLS-SEM method through a survey of 25 teachers. The results of this study indicated that teachers' emotional intelligence, principals' transformational leadership, and school organizational culture have a positive effect on teacher performance.